The relationship between the concentration of insulin-like growth factor, leptin and lipid metabolism indices in the blood of dairy cows during different physiological periods - M. R. Simonov; V. V. Vlizlo; T. О. Pundiak; B. V. Gutyj; L. G. Slivinska; I. I. Kovalchuk (Науковий вісник Львівського національного університету ветеринарної медицини та біотехнологій імені С.З. Ґжицького: Серія Ветеринарні науки)
Despite the evidence of the fundamental influence of the endocrine system on metabolism in ruminants, there is little literature on hormonal status. There is insufficient data on tissue hormones, particularly insulin-like growth factor and leptin. This work aimed to study the relationship between the concentration of insulin-like growth factor, leptin, and lipid metabolism indicators in the blood of cows during different physiological periods (end of dry period, beginning of lactation). The study was conducted in clinically healthy dairy cows. Blood samples were collected at different physiological periods: 7–10 days before calving, 2nd–4th, 10th–14th, and 30th–40th days of lactation. It was found that the highest lipid metabolism indices (total and esterified cholesterol, diglycerols, free fatty acids, triacylglycerols) were recorded in the blood of cows during the 10th to 14th day of lactation. At the same time, the concentration of insulin-like growth factor was also high, which positively correlated with the cholesterol and free fatty acids content. During this study period, the plasma concentration of leptin, on the contrary, was low. The highest leptin concentration was found at the end of the dry period (7–10 days before calving). On the 2nd–4th and 10th–14th days of lactation, a moderate negative correlation was found between the concentration of leptin and total cholesterol and between the concentration of leptin and insulin-like growth factor. Therefore, the positive correlation between the concentration of insulin-like growth factor and lipid metabolism indicators indicates a close relationship between the energy supply of the body, in particular through the release of initial metabolites of gluconeogenesis, and the level of somatomedin. On the contrary, high leptin levels before calving and low levels after calving help to prevent excessive obesity in cows before calving and increase feed intake at the beginning of lactation, when the need for nutrients is significant, since leptin is a peptide hormone of adipose tissue (adipokine) that acts on hypothalamic receptors, reducing appetite and increasing thermogenesis.